2013
DOI: 10.1017/s0016756813000472
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecology of the marine reptiles of the Redwater Shale Member of the Sundance Formation (Jurassic) of central Wyoming, USA

Abstract: The Redwater Shale Member (Oxfordian) of the Sundance Formation was deposited in the foreland basin of the Cordillera during the last and largest marine transgression of the Jurassic in North America. One ichthyosaur (Ophthalmosaurus natans), two cryptocleidoid plesiosaurs (Tatenectes laramiensis, Pantosaurus striatus) and one pliosauromorph (Megalneusaurus rex) are known from the Redwater Shale Member. Ichthyosaurs are much more abundant than plesiosaurs, making up almost 60% of the fauna. No actinopterygian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…As opposed to what was described for some ribs Massare et al 2014) and long bones (Houssaye et al 2014b), no general or local increase in bone compactness is observed in ichthyosaur vertebral centra, which are exclusively spongious, as compared to what is observed in most amniotes (Houssaye et al 2014a). As noted above, there is no peripheral layer of compact cortex as in most amniotes (Dumont et al 2013;Hayashi et al 2013;Houssaye et al 2014b).…”
Section: Mechanical Rolementioning
confidence: 75%
“…As opposed to what was described for some ribs Massare et al 2014) and long bones (Houssaye et al 2014b), no general or local increase in bone compactness is observed in ichthyosaur vertebral centra, which are exclusively spongious, as compared to what is observed in most amniotes (Houssaye et al 2014a). As noted above, there is no peripheral layer of compact cortex as in most amniotes (Dumont et al 2013;Hayashi et al 2013;Houssaye et al 2014b).…”
Section: Mechanical Rolementioning
confidence: 75%
“…The Rosso Ammonitico Formation is primarily representative of deep water column deposition (depth >110 m, Martire 1992;Martire et al 2006;Cau and Fanti 2011), thus significantly deeper than the epieric seas deposits where most metriorhynchoids and plesiosaurians are usually recovered (depth <50 m; Hudson and Martill 1991;Young et al 2010;Massare et al 2013). The taphonomy of both type specimens of Anguanax and Neptunidraco suggests that they did not suffer substantial transport neither disarticulation before burial (Cau andFanti 2011, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal ribs show variation in structure with length along the shaft as is also seen in mosasaurs, cetaceans and the ichthyopterygian Utatsusaurus hataii and ichthyosaurian Ophthalmosaurus natans (Houssaye & Bardet ; Massare et al . ; Nakajima et al . ; D'Emic et al .…”
Section: Discussionmentioning
confidence: 99%